PÓS-GRADUAÇÃO, PRODUÇÃO ACADÊMICA, INTERDISCIPLINARIDADE E SOCIALIZAÇÃO DO CONHECIMENTO: A PRODUÇÃO CIENTÍFICA DO GRANDE ABC À LUZ DO PNPG 2011-2020 - FEHLAUER, DENIS KONRADO (2016)
The objective of this investigation was to verify whether before autonomy and vocation that people have, as well as the possibility to receive government support and incentives, Universities within the great ABC area in São Paulo State, Brazil; meet the recommendations of the current PNPG (National Post Graduation - Graduate School - Plan). Therefore, fifty-eight dissertations and one thesis on applied social sciences published between 2011 and 2014 under the following educational institutions were analyzed - Universidade Metodista de São Paulo - UMESP (São Paulo Methodist University); Universidade Municipal de São Caetano do Sul - USCS (São Caetano do Sul University); Universidade Federal do ABC - UFABC (ABC Federal University, and Faculdade de Engenharia Industrial - FEI (Industrial Engineering College). The analysis was performed in the realm of four axis; two in the organizing PNPG 2011-2014 axis: the third axis was - the perfection of evaluation and its expansion into other system CT&I segments (Academic background for graduate school students directed toward extra academic activities and the business/corporate segment); and the fourth axis - the multiple and interdisciplinary factors between the main graduate school characteristics and important topics of research (such as promoting, by means of programs, concentration areas and research lines, the convergence of themes and problem sharing, opposing to its mere association or overlapping). The present study - qualitative, bibliographic, documental, exploratory, descriptive, state of knowledge type - was developed through a documental research method and categorial thematic content analysis. Data collecting was performed through digital repository of thesis and dissertations kept on internet base platforms by the Universities which scientific production was investigated. After data analysis, it was clearly demonstrated that approximately 68,96% of the scientific production in the applied social sciences, published by the Greater ABC Universities, between 2011 and 2014, correspond to the current PNPG expectations on regards to the constant recommendations of the third axis. In regards to the recommendations written in the fourth axis, we can see that around 31,03% of the selected research work meet the expectations of the Plan, presenting in its structure, according to the theoretical foundation used in this study, interdisciplinary characteristics